Pirfenidone Alleviates Against Fine Particulate Matter-Induced Pulmonary Fibrosis Modulating via TGF-β1/TAK1/MKK3/p38 MAPK Signaling Pathway in Rats - Jun-Seok Sung; Il-Gyu Ko; Lakkyong Hwang; Sang-Hoon Kim; Jin Hee Han; Jung Won Jeon; Sae Rom Kim; Jeong Mi Lee; Cheon Woong Choi (Biomedicines)
Increased exposure to particulate matter (PM) from air pollution causes lung inflammation and increases morbidity and mortality due to respiratory diseases. Pirfenidone is an anti-fibrotic agent used to treat idiopathic pulmonary fibrosis. Background/Objectives: In this experiment, we studied the therapeutic effects of pirfenidone on PM-induced pulmonary fibrosis. Methods: Pulmonary fibrosis was induced by the intratracheal application of 100 μg/kg PM10 mixed with 200 μL saline. After 42 days of PM10 infusion, 0.2 mL of distilled water with pirfenidone was orally administered to the pirfenidone-treated groups (200 and 400 mg/kg) every other day for a total of 15 times over 30 days. Results: The intratracheal administration of PM resulted in lung injury and a significant decrease in the number of bronchoalveolar lavage fluid cells. PM administration increased the lung injury score, level of lung fibrosis, and production of pro-inflammatory cytokines. Pirfenidone treatment effectively suppressed transforming growth factor-β-activated kinase 1 in PM-induced pulmonary fibrosis. The present changes inhibited the expressions of mitogen-activated protein kinase kinase 3 and p38, which suppressed transforming growth factor-β, ultimately alleviating lung fibrosis. PM exposure upregulated the expressions of fibronectin and type 1 collagen. PM exposure enhanced connective tissue growth factor and hydroxyproline levels in the lung tissue. The levels of these fibrosis-related factors were inhibited by pirfenidone treatment. Conclusions: These results suggest that pirfenidone is therapeutically effective against PM-induced pulmonary fibrosis.